Subspecies boundaries of the wild potatoes Solanum bulbocastanum and S. cardiophyllum based on morphological and nuclear RFLP data - Rodríguez, Aarón; Spooner, David M. (Instituto de Ecología, A.C., 2002)
Morphological data and single- to low-copy nuclear DNA restriction enzyme site data were used to test subspecies circumscriptions of Solanum bulbocastanum and S. cardiophyllum. A prior chloroplast DNA analysis showed these species to be part of two main clades: 1. S. bulbocastanum subsp. bulbocastanum, S. bulbocastanum subsp. dolichophyllum, S. bulbocastanum subsp. partitum, S. cardiophyllum subsp. cardiophyllum and S. cardiophyllum subsp. lanceolatum, and 2. S. cardiophyllum subsp. ehrenbergii and other Mexican diploid species. The nuclear DNA and morphological data showed S. cardiophyllum subsp. ehrenbergii to be slightly distinguishable from the other subspecies of S. cardiophyllum, and do not support the distinction of subspecies within either species. These data add to a growing body of evidence that there are too many wild potato taxa recognized.